Peningkatan Disiplin Guru SD Melalui Pelatihan Partisipatif Model In-On - Slameto, Slameto; Hardini, Agustina Tyas Asri; Prasetyo, Tego; Indarini, Endang (Kelola: Jurnal Manajemen Pendidikan, 2018)
This research is taken place to describe the punctual improvement of the teacher whoâs participated in participatory training model using in-on and to determine the influence of teacher optimism and teachers ability to give feedback, along with the contribution of each variable. This research was conducted based on the assessment of elementary school teachers who are participated in training for classroom action research preparation in KKG Gugus Joko Tingkir Salatiga, with 42 selected people randomly. Data for this research is quantitative. Data were collected through a self-rating scale of 21 items that proved to be valid and reliable. Data analysis using multiple linear regression with Stepwise Model. Based on the result of this research, it can be proved participatory training model effective in improving teacherâs punctual in teaching. There are 2 variables/predictors of teacher optimism and or together with their ability to provide feedback on teacherâs punctual in teaching. Teachers optimism has an effect (positive and significant) on teacherâs punctual in teaching equal to 35.20%. Teacherâs optimism along with their ability to give feedback impact teacherâs punctual in teaching as much as 42.9%. Thus participatory training model should be applying learning principles that emphasize positive optimistic psychology, get used to working effectively with challenges, have the confidence to use innovative thinking in achieving success.